Hello from MrBillDoesMath!
Answer:
See answers below in Discussion section.
Discussion:
#1
(7x + 4) - (2x + 9) =
(7x - 2x) + (4 - 9 ) =
5x -5
#10
(5x^4 - 2x^2) - (3x - 2x^2 - 4x^3 + 6x^4) = => combine like terms
x^4(5 - 6) + x^3(4) + x^2(-2+2) + x(-3) = => as =2 +2 = 0
=-x^4 + 4x^3 + x^2(0) + (-3)x =
= -x^4 + 4x^3 - 3x
#11
(3x^2 + 7xy - 2y^2) - (x^2 - 6xy + 2y^2) =
x^2(3-1) + xy(7+6) + y^2(-2-2) =
2x^2 + 13xy -4 y^2
#12
(-x^2 - 9xy+5y^2) - (4x^2 -2xy -y^2)
x^2 ( -1 -4) + xy(-9 +2) + y^2(5+1) =
-5x^2 -7xy + 6y^2
Thank you,
MrB